Will climate change increase ozone depletion from low-energy-electron precipitation? - A. J. G. Baumgaertner; P. Jöckel; M. Dameris; P. J. Crutzen (Atmospheric Chemistry and Physics, 2010)
We investigate the effects of a strengthened stratospheric/mesospheric residual circulation on the transport of nitric oxide (NO) produced by energetic particle precipitation. During periods of high geomagnetic activity, energetic electron precipitation (EEP) is responsible for winter time ozone loss in the polar middle atmosphere between 1 and 6 hPa. However, as climate change is expected to increase the strength of the Brewer-Dobson circulation including extratropical downwelling, the enhancements of EEP NOx concentrations are expected to be transported to lower altitudes in extratropical regions, becoming more significant in the ozone budget. Changes in the mesospheric residual circulation are also considered. We use simulations with the chemistry climate model system EMAC to compare present day effects of EEP NOx with expected effects in a climate change scenario for the year 2100. In years of strong geomagnetic activity, similar to that observed in 2003, an additional polar ozone loss of up to 0.4 μmol/mol at 5 hPa is found in the Southern Hemisphere. However, this would be approximately compensated by an ozone enhancement originating from a stronger poleward transport of ozone from lower latitudes caused by a strengthened Brewer-Dobson circulation, as well as by slower photochemical ozone loss reactions in a stratosphere cooled by risen greenhouse gas concentrations. In the Northern Hemisphere the EEP NOx effect appears to lose importance due to the different nature of the climate-change induced circulation changes.